UNDOCKING AND COLLISION: THE RECENT PATHS OF THE SEMIPERIPHERY IN THE WORLD-SYSTEM - Vieira, Maíra Baé Baladão (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The concept of semiperiphery is considered by many authors as the most important contribution of Immanuel Wallerstein’s work. Since its definition in the 1970s, strenuous attempts have been made to define a geographical dimension. This article seeks to retake the relevance of the semiperiphery to the understanding of contemporary international circumstances. Its operation allows global data to be aggregated, offering a factual and updated cut of the most diverse economic and political facets that make up the World-System. To define which countries make up the semiperiphery in the present time, one of the attempts is replicated and an update of the listing is presented. In the end, some examples of instrumentation of the concept are presented, based on selected indicators.